Methanol Vapor Sensing by Porous Silicon - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2014)
In this study, methanol vapor sensing of porous silicon was investigated. The porous silicon samples were anodized in HF based solution and rinsed with ethanol or deionized water after the anodisation. Porous silicon surface is very sensitive for methanol vapor sensing and the sensitivity affect from the rinsing procedure of porous silicon. The experimental results show that porous silicon is a promising candidate material for sensing methanol vapor.
Keywords: GAS SENSOR; PALLADIUM